Altered GABAergic signaling and chloride homeostasis in eye movement circuits during late neurodevelopment: implications for Alzheimer’s disease therapy - Porcher, Christophe; Rivera, Claudio; Medina, Igor; Koric, Lejla (Frontiers in Pharmacology, 2025)
Eye movement deficits, including abnormal saccades and impaired smooth pursuits, are among the earliest observable indicators of neurodegenerative diseases, particularly Alzheimer’s disease (AD). These deficits arise from dysfunctions in neural circuits controlling oculomotor function, including the superior colliculus, parietal and frontal eye fields, cerebellum, and locus coeruleus (LC). Since these circuits rely on a delicate balance of excitation and inhibition (E/I), their impairment reflects broader neural dysregulation seen in neurodegenerative diseases. Notably, oculomotor abnormalities strongly correlate with cognitive decline and the progression of neuropathological hallmarks, highlighting their potential as sensitive, non-invasive clinical markers for early detection. GABAergic signaling, the principal mechanism of inhibitory neurotransmission, plays a central role in maintaining E/I balance and regulating neural network activity. In neurodegenerative diseases, GABAergic dysfunction is characterized by reduced GABA levels, altered GABAA receptor function, and compromised inhibitory control. These changes drive network hyperexcitability, synaptic instability, and cognitive impairments. Such disruptions are particularly impactful in oculomotor circuits, contributing directly to eye movement deficits. The potassium-chloride co-transporter 2 (KCC2), a key regulator of intracellular chloride homeostasis, is essential for maintaining GABAergic inhibition. In AD, KCC2 dysfunction exacerbates GABAergic dysregulation, amplifying E/I imbalance and impairing neural circuits. This review integrates current findings on GABAergic signaling, KCC2 dysfunction, and oculomotor deficits in AD, offering novel insights into the mechanisms linking KCC2 dysfunction and oculomotor impairments within the context of AD.